A retinal origin of nystagmus—a perspective - Kamermans, Maarten; Winkelman, Beerend H. J.; Hölzel, M-B.; Howlett, Marcus H. C.; Kamermans, Wouter; Simonsz, H. J.; de Zeeuw, C. I. (Frontiers in Ophthalmology, 2023)
Congenital nystagmus is a condition where the eyes of patients oscillate, mostly horizontally, with a frequency of between 2 and 10 Hz. Historically, nystagmus is believed to be caused by a maladaptation of the oculomotor system and is thus considered a disease of the brain stem. However, we have recently shown that congenital nystagmus associated with congenital stationary night blindness is caused by synchronously oscillating retinal ganglion cells. In this perspective article, we discuss how some details of nystagmus can be accounted for by the retinal mechanism we propose.